2020
DOI: 10.1002/cctc.201902028
|View full text |Cite
|
Sign up to set email alerts
|

Hydroconversion of 5‐Hydroxymethylfurfural to 2,5‐Dimethylfuran and 2,5‐Dimethyltetrahydrofuran over Non‐promoted Ni/SBA‐15

Abstract: The selective hydroconversion of 5‐hydroxymethylfurfural (HMF) to biofuels is currently highly sought‐for. While the literature has demonstrated that this reaction is possible on promoted Ni catalysts, we show here that a monometallic, non‐promoted Ni/SBA‐15 catalyst, prepared by incipient wetness impregnation, can convert HMF to 2,5‐dimethylfuran (DMF) and to 2,5‐dimethyltetrahydrofuran (DMTHF) at 180 °C, in a consecutive way. Through a control over reaction time, high yields to DMF (71 %, at conversion of 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…There are two groups of catalysts which have been proposed for conversion of HMF to DMF: 1) Pd, Pt, Ru, Ir, Co, Ni and Cu-based monometallic or bimetallic catalysts, which perform hydrogenolysis of C-O bond at the temperatures in the range of 150~250 o C. [14,[18][19][20][21][22][23] and 2) bifunctional metal-acid catalysts for hydrodeoxygenation through protonation of the hydroxyl groups and dehydration at milder reaction conditions (60~130 o C) [24][25][26][27][28][29][30][31][32][33] . The disadvantage of the first route is that the high reaction temperature induces polymerization of highly reactive HMF to humins [34] .…”
Section: Introductionmentioning
confidence: 99%
“…There are two groups of catalysts which have been proposed for conversion of HMF to DMF: 1) Pd, Pt, Ru, Ir, Co, Ni and Cu-based monometallic or bimetallic catalysts, which perform hydrogenolysis of C-O bond at the temperatures in the range of 150~250 o C. [14,[18][19][20][21][22][23] and 2) bifunctional metal-acid catalysts for hydrodeoxygenation through protonation of the hydroxyl groups and dehydration at milder reaction conditions (60~130 o C) [24][25][26][27][28][29][30][31][32][33] . The disadvantage of the first route is that the high reaction temperature induces polymerization of highly reactive HMF to humins [34] .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the conversion of HMF to valuable products has attracted much attention. Up to now, it has been reported that many chemicals such as 2,5-dimethylfuran (DMF) [18][19][20][21], furan-2,5-diyldimethanol (DHMF) [22,23], furan-2,5-dicarbaldehyde [24][25][26], furan-2,5-dicarboxylic acid [27][28][29][30][31], cyclopentanone derivatives [32][33][34][35][36][37][38], acyclic 2,5-diketones [39][40][41] and so on [42][43][44][45][46][47] can be obtained from HMF through hydrogenation, oxidation and other catalytic processes. The acyclic 2,5-diketones, derived from the hydrogenation of HMF, are valuable intermediates with widespread applications in polymers, surfactants, medicine and solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the critical derivatives of HMF involve redox chemistry, where the existing functional groups in HMF (i.e., hydroxymethyl, aldehyde, furan ring) are selectively oxidized/ reduced to other functional groups. 236,237 The sequential reduction of HMF under catalytic hydrogenation conditions leads to a series of furanic and non-furanic derivatives (Scheme 6). For example, selective hydrogenolysis of the C-OH bond in HMF forms 5-methylfurfural (MF).…”
Section: Oxidation Of Ismentioning
confidence: 99%